The Intelligence of Co-opetition- Toyota's Way - Chen, Yeh-Ying (2011)
With the highly globalised market and the increasingly saturated market, the traditional thinking of business has been changing. It seems true that competition and cooperation are two sharp contrasts indicating the different approaches of business strategy formulation. Nowadays, a new way of business approach-co-opetition has gradually raised the attention among every industry. This paper aims to illustrate Toyota‟s performance by analysing its resources, which underpins its organisational capabilities, industry trend, which forms competitive advantages, and finally speculating the development possibility and in turn, preventing from potential threats. Toyota, one of the world‟s leading automakers, possesses outstanding performance in the highly competitive automotive industry. Its competitive capabilities are known as Toyota Production System (TPS), which act as a backbone of the whole Toyota Group, and consolidate its leading position. This paper examines the hidden secret of Toyota Business Empire by resource-based view, industry-based view and follows by SWOT analysis. Its successful performance is summarised as co-opetition intelligence that strategically competes and cooperate .with rivals at the same time. The findings of this paper show the symbiosis of competition and cooperation, and also bring up the attention of interfirm value creation. By co-opetition strategy, the game of business is not only a one-way thinking but a multiple dimensions due to the multiple roles a firm can play at the same time. Importantly, the interfirm collaboration creates infinity business opportunities and extends the existing limited market.